Implementasi Pengorganisasian Dakwah dalam Masyarakat Plural: Tantangan dan Peluang - Muhammad Fauzan; Setiawan Tri Admaja; Andini Andini (Pusat Riset dan Inovasi Nasional, 2025)
This article examines the implementation of da'wah organizations in pluralistic societies, highlighting the challenges and opportunities they present. Da'wah is important to convey religious values and guide people towards goodness. However, in such societies, differences in beliefs can cause social friction. Effective da'wah strategies are influenced by communication styles, methods, and societal contexts. Challenges include misunderstandings, negative stereotypes, and limited access to diverse communities. This article emphasizes the need for a dialogue-based approach and adapting to societal needs to promote peace in diverse environments. Understanding the intricacies of da'wah organizations can enhance interfaith understanding and community solidarity. Effective da'wah implementation can foster a harmonious society enriched by Islamic values in a pluralistic context.